Amortyzacja jako instrument optymalizacji podatkowej - Kluzek, Marta (Depreciation as a Tool of Tax Optimalization, 2007)
The article shows the meaning of tax optimalization and its effects on a company. It is a part of a strategic planning because most financial and investment decisions involve taxation consequences. Tax optimalization can reduce the tax burden and therefore increase the net income. One of very interesting instruments used to reduce tax liabilities is depreciation. But we should include effects of using tax instruments in a long-term business plan to estimate their real effects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 186-194